Antiviral Activities of Indonesian Medicinal Plants in the East Java Region Against Hepatitis C Virus - Achmad Fuad (BioMed Central, 2013)
Background Hepatitis C virus (HCV) is a major cause of liver disease and a potential cause of substantial morbidity and mortality worldwide. The overall prevalence of HCV infection is 2%, representing 120 million people worldwide. Current standard treatment using pegylated interferon and ribavirin is effective in only 50% of the patients infected with HCV genotype 1, and is associated with significant side effects. Therefore, it is still of importance to develop new drugs for treatment of HCV. Antiviral substances obtained from natural products, including medicinal plants, are potentially good targets to study. In this study, we evaluated Indonesian medicinal plants for their anti-HCV activities.